2000
DOI: 10.1161/01.cir.102.21.2672-c
|View full text |Cite
|
Sign up to set email alerts
|

The Department of Veterans Affairs Aneurysm Detection and Management (ADAM) Study.

Abstract: Background:In the treatment of patients with unstable angina and non-ST segment elevation myocardial infarction (UA/NSTEMI), debate exists as to whether an early invasive vs. a conservative strategy is optimal therapy. Methods: In the international TACTICS-TIMI 18 trial, 2220 patients with UA/NSTEMI who had either electrocardiographic changes, elevated cardiac markers or a history of prior coronary artery disease, were immediately treated with aspirin, heparin and the glycoprotein (GP) IIb/IIIa inhibitor tirof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 0 publications
0
32
1
Order By: Relevance
“…29 Current guidelines on surgical management of AAA, with surveillance advised for AAA < 5.5 cm in diameter, have mainly been drawn from the UKSAT and ADAM trial. 8,30 Although in these trials the population samples consisted of 83% and 99.2% male patients, respectively, in the former study it was observed that risk of rupture in women was 4 times higher than men (HR: 4.0; 95% CI: 2.0-7.9). Brown and Powell 19 also demonstrated that in women, the AAAs that ruptured were on average smaller than AAA in men [5.0 (4.2-5.8) versus 6.0 (4.6-7.4)].…”
Section: Gendermentioning
confidence: 94%
See 1 more Smart Citation
“…29 Current guidelines on surgical management of AAA, with surveillance advised for AAA < 5.5 cm in diameter, have mainly been drawn from the UKSAT and ADAM trial. 8,30 Although in these trials the population samples consisted of 83% and 99.2% male patients, respectively, in the former study it was observed that risk of rupture in women was 4 times higher than men (HR: 4.0; 95% CI: 2.0-7.9). Brown and Powell 19 also demonstrated that in women, the AAAs that ruptured were on average smaller than AAA in men [5.0 (4.2-5.8) versus 6.0 (4.6-7.4)].…”
Section: Gendermentioning
confidence: 94%
“…The Aneurysm Detection and Management (ADAM) trial demonstrated similar results, with a mortality rate one third that of the UKSAT trial (relative risk in the immediate-repair group as compared with the surveillance group, 1.21; 95% CI: 0.95-1.54). 8 Thus, it was concluded that survival is not improved by elective repair of AAA measuring less than 5.5 cm, even when operative mortality is low.…”
Section: Aneurysm Sizementioning
confidence: 99%
“…A large-scale randomized trial has shown that elective repair is only beneficial once an AAA has reached a diameter greater than 5.5 cm. 31 The first reported rupture of an AAA after SWL was in 1991 when an elderly patient with a large aneurysm of 10 cm presented 5 days after SWL; no operative management was sought, and the rupture proved fatal. 32 Initially, this patient had presented with left lower limb neurology 5 days after SWL before sudden onset back pain and cardiorespiratory collapse developed.…”
Section: Rupture Of Aaa After Swlmentioning
confidence: 99%
“…5 The prevalence of AAA is 3% to 10% in those older than 50 years and varies based on the prevalence of risk factors in the population. [6][7][8][9][10][11][12] Men are 5 times as likely as women to have an AAA with a prevalence of 3% to 10% compared with only 1% to 2% for women. The most important modifiable risk factor is smoking; smokers are approximately 5 times as likely as nonsmokers to develop AAA.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…14 Other risk factors are hypertensionandwhiterace. 8 Diabeteshasbeenfoundtobeprotective, with half the risk of developing AAA. 8 Mr F's profile fits these criteria as a man older than 50 years with hypertension who has smoked for many years and continues to smoke.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%